Research methods in social science - "Majumdar, P. K." (New Delhi, 2005)
An ardent reader in social science today takes as much interest in the research conclusions as the methods by which they are arrived at. Increasingly, the merit of a research is judged not by conclusions but by the design of the research and the assumptions the researcher makes about his method and data, method of selection of the sample, controls exercised at different stages of the study, the nature of measurements involved and the statistical/mathematical models used in comprehensive understanding of this vastly complex social world. The managerial skill of the researcher is increasingly drawing attention. This book gives a cogent exposition of the methodological issues in social research to the beginners. A budding scientist becomes perplexed with bewildering array of techniques and methodologies applied in social and behavioral research. The book tries to answer many of the questions that overwhelm a young researcher when confronted with diverse issues and techniques employed in social research. The book highlights the norms and the rules a research scientist ought to adhere in a social discourse and it also delves with issues like "Why study research methodology?" to most of the conventional topics as research design, sampling, data collection techniques, scaling and measurement issues, data analysis and data storing using computer support.
Keywords: Social sciences-Research